2023
DOI: 10.3389/fendo.2023.1194425
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein levels modulate the gut microbiome composition through fecal samples derived from lactating ewes

Jiachong Liang,
Sikandar Ali,
Chunrong Lv
et al.

Abstract: In ruminants, the digestion and utilization of dietary proteins are closely linked to the bacterial populations that are present in the gastrointestinal tract. In the present study, 16S rDNA sequencing, together with a metagenomic strategy was used to characterize the fecal bacteria of ewes in the early lactation stage after feeding with three levels of dietary proteins 8.58%, 10.34%, and 13.93%, in three different groups (H_1), (H_m) and (H_h), respectively. A total of 376,278,516 clean data-points were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Dietary protein is a major nutrient that provides amino acids for several metabolic pathways involved in tissue synthesis, regulation of metabolic processes, and immune as well as redox strengthening, which ultimately improves the growth performance of the ruminants [ 19 , 20 ]. In our recently published work, we evaluated how dietary protein levels (same diets as used in this experiment) change the fecal bacterial composition and found that changes in dietary protein contents altered rumen microbiota composition [ 17 ] and consequently influenced the growth performance, milk production, and blood biochemical indices [ 18 ] of the nursing ewes. Further, it is well established that dietary protein levels influence growth performance by altering the microbial and enzymatic function of sheep and cattle [ 5 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dietary protein is a major nutrient that provides amino acids for several metabolic pathways involved in tissue synthesis, regulation of metabolic processes, and immune as well as redox strengthening, which ultimately improves the growth performance of the ruminants [ 19 , 20 ]. In our recently published work, we evaluated how dietary protein levels (same diets as used in this experiment) change the fecal bacterial composition and found that changes in dietary protein contents altered rumen microbiota composition [ 17 ] and consequently influenced the growth performance, milk production, and blood biochemical indices [ 18 ] of the nursing ewes. Further, it is well established that dietary protein levels influence growth performance by altering the microbial and enzymatic function of sheep and cattle [ 5 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, aspartic acid, phenylethylamine, tyrosine, tryptophan, and methionine sulfoxide showed significant differences between the different groups, and notably, all these metabolites showed a clear increasing trend with increasing dietary protein levels. The difference between groups can be associated with the differences in dietary protein levels as it is well known that dietary protein contents provide nitrogen bases as well as amino acids for metabolism [ 17 ]. Regarding the amino-acid compounds, it is established that there are correlations with the dietary protein levels as followed by the nursing ewes in the current experiment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations